IPO initial returns in China: Underpricing or overvaluation? - Shunlin Song; JinSong Tan; Yang Yi (China Journal of Accounting Research, 2014)
This paper separates the amount of IPO underpricing (primary market underpricing) and overvaluation (secondary market overvaluation) from the value of an IPO's initial return to evaluate the relative importance of these two factors and their main determinants. Using data on the IPOs of 948 Chinese firms, we find that average initial returns are 66% and that underpricing and overvaluation are between 14-22% and 44-53%, respectively, depending on the method used to assess firms' intrinsic values. In addition, while both the value of the initial return and the extent of overvaluation are significantly negatively related to post-IPO long-run stock performance, overvaluation can predict post-IPO performance better than the value of the initial return. Value uncertainty in IPOs is positively related to both underpricing and overvaluation, and both the underwriter's reputation and the existence of pricing regulation are positively related to underpricing. Investor sentiment has a positive effect on overvaluation but has no effect or a negative effect on underpricing. Overall, our results suggest that in China overvaluation accounts for a larger proportion of the initial return than underpricing, and that underpricing and overvaluation have different determinants.
Keywords: G14; G30; G39; 650; IPO initial return; IPO underpricing; IPO overvaluation; Post-IPO long-run stockperformance; Determinants